Numerical Response Surfaces of Volume of Ablation and Retropulsion Amplitude by Settings of Ho:YAG Laser Lithotripter. (7th March 2018) - Zhang, Jian J.; Rutherford, Jonathan; Solomon, Metasebya; Cheng, Brian; Xuan, Jason R.; Gong, Jason; Yu, Honggang; Xia, Michael L. D.; Yang, Xirong; Hasenberg, Thomas; Curran, Sean
Abstract : Objectives. Although laser lithotripsy is now the preferred treatment option for urolithiasis due to shorter operation time and a better stone-free rate, the optimal laser settings for URS (ureteroscopic lithotripsy) for less operation time remain unclear. The aim of this study was to look for quantitative responses of calculus ablation and retropulsion by performing operator-independent experiments to determine the best fit versus the pulse energy, pulse width, and the number of pulses. Methods. A lab-built Ho:YAG laser was used as the laser pulse source, with a pulse energy from 0.2 J up to 3.0 J and a pulse width of 150 μ s up to 1000 μ s. The retropulsion was monitored using a high-speed camera, and the laser-induced craters were evaluated with a 3-D digital microscope. The best fit to the experimental data is done by a design of experiment software. Results. The numerical formulas for the response surfaces of ablation speed and retropulsion amplitude are generated. Conclusions. The longer the pulse, the less the ablation or retropulsion, while the longer pulse makes the ablation decrease faster than the retropulsion. The best quadratic fit of the response surface for the volume of ablation varied nonlinearly with pulse duration and pulse number.